Supraglottic jet oxygenation and ventilation via nasopharyngeal airway for a patient with iatrogenic tracheoesophageal fistula: A case report - Gu, Yang; Zhang, Xiaowei; Min, Keting; Wei, Juan; Zhou, Qing; Lv, Xin; Duan, Ruowang (Frontiers in Medicine, 2023)
Background: Iatrogenic tracheoesophageal fistula (TEF) is a rare but life-threatening condition. No consensus has been reached regarding TEF treatment, though, stenting has been gaining popularity for less invasiveness than thoracic surgery. The airway management during stent placement for TEF could be challenging. Case presentations: We report a patient who suffered from TEF after cardiac surgery with symptoms of persistent coughing and aspiration. He who was admitted for stent placement but ended up in failure and referred to our institution for further treatment. We successfully took advantage of the supraglottic jet oxygenation and ventilation (SJOV) during stent placement. Conclusion: This is the first case so far describing SJOV in complicated stenting treatment. This demonstrates that SJOV can be applied for stent placement in TEF patients with restricted airways.